HOW CAN URBANIZATION BE SUSTAINABLE? A REFLECTION ON THE ROLE OF CITY RESOURCES IN GLOBAL SUSTAINABLE DEVELOPMENT - Pereira Roders, Ana (BDC. Bollettino Del Centro Calza Bini, 2013)
This article is a contribution to the debate on the role of city resources in global sustainable development. It discusses the evolution of models in which urbanization is defined to be sustainable, as well as, their relation to the conservation of city resources. Further, it provides an in-depth reflection on the UNESCO Recommendation on the Historic Urban Landscape, reviewing its elaboration and implementation, both in practice and research. The results are expected to help government officials, academics, activists, or interested citizens identify and address the sustainability of urbanization, as well as, discuss the role of conservation of city resources in global sustainable development.